2006
DOI: 10.1002/uog.2718
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intraobserver variability in sonographic measurement of the lower uterine segment after a previous Cesarean section

Abstract: The agreement between two observers for sonographic transvaginal measurement of the lower uterine segment can be considered good, compared with poor to moderate agreement using the transabdominal approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 9 publications
10
57
1
3
Order By: Relevance
“…Based on the previous studies [13][14][15][16], a sample size of 34 women in each group was required to compare the difference in mean LUS thickness, for an a of 0.05 and a power of 0.80, with an anticipated difference in mean LUS thickness of 0.4 mm and an anticipated SD of 0.8 mm. Considering 10 % rate of spontaneous labor before surgery and any loss to follow up, a total of 50 women were selected in each group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previous studies [13][14][15][16], a sample size of 34 women in each group was required to compare the difference in mean LUS thickness, for an a of 0.05 and a power of 0.80, with an anticipated difference in mean LUS thickness of 0.4 mm and an anticipated SD of 0.8 mm. Considering 10 % rate of spontaneous labor before surgery and any loss to follow up, a total of 50 women were selected in each group.…”
Section: Methodsmentioning
confidence: 99%
“…2; ROC curve) as measured by TAS. Rozenberg et al [8] and Jastrow et al [16] had proposed cut off of 3.5 mm for LUS thickness above which VBAC can be safely offered to women with previous CS. We also observed that in all women with LUS grades III & IV, LUS thickness (as measured by TAS and TVS) was less than 3 mm.…”
mentioning
confidence: 99%
“…However, one study reported on the thickness of the myometrium at 36-38 gestational weeks in nulliparous women and in parous women who had only delivered vaginally [35]. The reproducibility of ultrasound measurements of the thickness of the lower uterine segment using different examination techniques has been examined in five studies [41] [ 45,46,48,49]. To sum up, most intra-and inter-observer differences were <1 mm [46,49], but the limits of agreement (the limits within which 95% of future measurements are expected to fall) were wide, i.e up to 4 mm for full lower uterine thickness and up to 1.5 mm for myometrial thickness [48].…”
Section: B How Should the Thickness Of The Lower Uterine Segment Durimentioning
confidence: 99%
“…The reproducibility of ultrasound measurements of the thickness of the lower uterine segment using different examination techniques has been examined in five studies [41] [ 45,46,48,49]. To sum up, most intra-and inter-observer differences were <1 mm [46,49], but the limits of agreement (the limits within which 95% of future measurements are expected to fall) were wide, i.e up to 4 mm for full lower uterine thickness and up to 1.5 mm for myometrial thickness [48]. Despite the imprecision in the measurements, the intra-and inter-observer agreement with regard to classifying the lower uterine segment as being thicker or thinner than a certain cutoff level was at least moderate in most studies, reported Kappa values ranging from 0.34 -1.0.…”
Section: B How Should the Thickness Of The Lower Uterine Segment Durimentioning
confidence: 99%
“…Additionally, the need for external validation is shown when looking into studies on inter-and intraobserver validity of the RMT measurements. These studies use cut-off values of 2.4-3.5 mm for evaluating reproducibility and state that overall interobserver differences are ≤ 1 mm for 77.5-88% of observers 5,6 . However, in the model RMT is entered in millimeters while predicted probability increases per millimeter with a coefficient (beta) of 1.44.…”
Section: Re: Predicting Successful Vaginal Birth After Cesarean Sectimentioning
confidence: 99%